Red Yeast Rice for Hypercholesterolemia - Cicero, Arrigo F.G. (Methodist Debakey Cardiovasc J, 2019)
The extract of red yeast rice (RYR) is the most effective cholesterol-lowering nutraceutical on the market. In particular, its effectiveness is directly related to the amount of monacolin K within the extract (up to 10 mg/day). Consuming monacolin K on a daily basis reduces low-density lipoprotein (LDL) cholesterol plasma levels between 15% and 25% within 6 to 8 weeks. Certainly, the decrease in LDL-cholesterol is accompanied by a similar reduction in total cholesterol, non–high-density lipoprotein cholesterol, plasma apolipoprotein B, matrix metalloproteinases 2 and 9, and high-sensitivity C-reactive protein. Furthermore, the RYR lipid-lowering effect is associated with significant improvements in pulse wave velocity and endothelial function, which are validated and reliable biomarker tools able to detect vascular aging. Although it has a mechanism of action similar to statins, a daily consumption of between 3 and 10 mg monacolin K has only minimal associated risks, and mild myalgias are seen only in the frailest patients (those who also cannot tolerate minimal dosages of statin). The monacolin K found in RYR is a safe and effective supplement for managing mild to moderate hypercholesterolemia in people with no additional cardiovascular risk factors.